2017
DOI: 10.1073/pnas.1705642114
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanical response of double-stranded DNA and RNA under constant stretching forces using all-atom molecular dynamics

Abstract: Multiple biological processes involve the stretching of nucleic acids (NAs). Stretching forces induce local changes in the molecule structure, inhibiting or promoting the binding of proteins, which ultimately affects their functionality. Understanding how a force induces changes in the structure of NAs at the atomic level is a challenge. Here, we use all-atom, microsecond-long molecular dynamics to simulate the structure of dsDNA and dsRNA subjected to stretching forces up to 20 pN. We determine all of the ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
153
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(166 citation statements)
references
References 46 publications
13
153
0
Order By: Relevance
“…The calculated torsional modulus for all oligomers shows a crossover from the relatively soft value of around 30-60 nm at the single base-pair level to a large-scale asymptotic value between 90 and 100 nm (see Table 1), which is in agreement with previous study. 25 While softer values at short length scales are consistent with fluorescence polarization anisotropy measurements, 58,59 small-angle X-ray scattering (SAXS), 31 analysis of crystallographic DNA structures 29 and many calculations from MD, 21,26,30 stiffer magnitudes concur with single-molecule experiments 8,13,14 and other modelling estimations 19,60,61 at longer length scales. Values calculated for the whole segment also fall within the long-scale range between 90-100 nm (see Table 1), achieving an overall good convergence on the microsecond-long trajectories ( Figure S1) Persistence length.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The calculated torsional modulus for all oligomers shows a crossover from the relatively soft value of around 30-60 nm at the single base-pair level to a large-scale asymptotic value between 90 and 100 nm (see Table 1), which is in agreement with previous study. 25 While softer values at short length scales are consistent with fluorescence polarization anisotropy measurements, 58,59 small-angle X-ray scattering (SAXS), 31 analysis of crystallographic DNA structures 29 and many calculations from MD, 21,26,30 stiffer magnitudes concur with single-molecule experiments 8,13,14 and other modelling estimations 19,60,61 at longer length scales. Values calculated for the whole segment also fall within the long-scale range between 90-100 nm (see Table 1), achieving an overall good convergence on the microsecond-long trajectories ( Figure S1) Persistence length.…”
Section: Resultssupporting
confidence: 60%
“…16,17 In addition, it has been very difficult to identify the mechanisms through which some short sequence motifs, like A-tracts, originate extraordinary bending. 18 On these matters, molecular dynamics (MD) simulations at atomic resolution have become an impressive source of new important information, 19 that have provided (i) a systematic analysis of elasticity at the dinucleotide levels, 20,21 (ii) an evaluation of the influence of nearest flanking basepairs up to the our knowledge, there is no other program that estimates bulk flexibility constants from ensembles obtained by numerical simulations and that uncovers systematically how these properties emerge from local fluctuations. We also believe that for the first time, dependence of elasticity on sequence is exhaustive evaluated in this paper, particularly at the tetranucleotide level thanks to analysing the ABC trajectory database.…”
Section: Introductionmentioning
confidence: 99%
“…Using constant-force molecular dynamics (MD) simulations [14], we observed that the extension of the DNA changed from one sequence to another for molecules with the same number of base pairs. We performed over 1 μs-long MD simulations of 18 base pair long DNA molecules with benchmark sequences of the form CGCGðNNÞ 5 CGCG, where NN denotes AA, AC, AG, AT, CG, and GG, and computed its average structure at 1 pN force, see Fig.…”
mentioning
confidence: 99%
“…Using constant-force molecular dynamics (MD) simulations (14) we observed that the extension of the DNA changed from one sequence to another for molecules with the same number of base pairs. we observed that the extension of the DNA changed from one sequence to another for molecules with the same number of base pairs.…”
mentioning
confidence: 99%
“…represents an estimation of nucleosome curvature according to (28). b, The computed value of is plotted as a function of the value directly measured from the force-extension curve as done in (14). The stretch modulus was computed from our model for the simulated sequences described above using Eq.…”
mentioning
confidence: 99%